MESIN PELARUT PCB BERBASIS PLC DENGAN BAHAN PELARUT HCl DAN H2O2 - , BACHTIAR DUMAIS LAKSANA, Ir. Lukman Subekti, M.T. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Printed Circuit Board or PCB is abbreviated as one important component in the fields of electronics that is used to make a circuit or electronic circuit, where the PCB schematic arrangement of a place or track foot - foot component. To mandapatkan pathway components that we want then be made to track the way menyablon on the side of the copper plate and then diluted using chemical solvents for copper, which is commonly used is FeCl3 (Ferry chloride). This final examination explores the PCB Automatic Solvent is used to assist the process of dissolving PCB automatically without any manual intervention and it takes a lot of time by using a chemical solution of HCl and H2O2. This tool is made with components such as microcontroller and PLC controller to help measure the acidity and move the rotating equipment, as well as include other instruments such as the LCD Display to help reading kkerja status tool. Automatic Solvent PCB has two functions work, which every function is regulated by acidity range solution that would determine the execution output.